2019
DOI: 10.1177/1747021819844219
|View full text |Cite
|
Sign up to set email alerts
|

Predictably confirmatory: The influence of stereotypes during decisional processing

Abstract: Stereotypes facilitate the processing of expectancy-consistent (vs expectancy-inconsistent) information, yet the underlying origin of this congruency effect remains unknown. As such, here we sought to identify the cognitive operations through which stereotypes influence decisional processing. In six experiments, participants responded to stimuli that were consistent or inconsistent with respect to prevailing gender stereotypes. To identify the processes underpinning task performance, responses were submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 96 publications
4
33
1
Order By: Relevance
“…Rather, primes enhanced the processing of stereotype-inconsistent compared with stereotype-consistent targets. Albeit using a different experimental paradigm (i.e., explicit face-label stereotype-based judgement task), Falbén et al (2019) recently reported an identical effect. To guide social-cognitive functioning in an adaptable manner, the mind must possess two complementary skills (see Grossberg, 1987 ; Johnston & Hawley, 1994 ; McClelland et al, 1995 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rather, primes enhanced the processing of stereotype-inconsistent compared with stereotype-consistent targets. Albeit using a different experimental paradigm (i.e., explicit face-label stereotype-based judgement task), Falbén et al (2019) recently reported an identical effect. To guide social-cognitive functioning in an adaptable manner, the mind must possess two complementary skills (see Grossberg, 1987 ; Johnston & Hawley, 1994 ; McClelland et al, 1995 ).…”
Section: Discussionmentioning
confidence: 95%
“…For model 8, the posterior distributions of the estimated parameters were used to simulate data sets. We then assessed the quality of model fit by plotting the observed data against the simulated data for the .1, .3, .5, .7, and .9 response time quantiles for each experimental condition ( Falbén et al, 2019 ; Krypotos et al, 2015 ). As can be seen in Figure 1 , with nearly complete overlap between the observed values and the simulated estimates across all prime-target combinations, this revealed good model fit.…”
Section: Resultsmentioning
confidence: 99%
“…N. White & Poldrack, 2014). Adopting this analytical approach, recent work has traced stereotype priming to the operation of a response bias (Falbén et al, 2019;Tsamadi et al, 2020). Tsamadi et al (2020), for example, required participants to report the stereotype-related status of object labels (e.g., flower, briefcase) that followed female or male facial primes.…”
Section: Exploring Stereotype-based Primingmentioning
confidence: 99%
“…Multiple versions of the grids were created for each priming condition (i.e., 1, 2, 3, or 4 faces) to ensure that faces appeared equally often at each of the locations during the task. The to-be-judged occupations were taken from Falbén et al (2019) and the objects from Crawford et al (2004). On completion of the task, participants were debriefed, thanked, and dismissed.…”
Section: Stimulus Materials and Proceduresmentioning
confidence: 99%
“…The human preference for consistent and predictable social interactions has long been acknowledged as a core motivational component driving everyday behavior (Festinger, 1957; Gawronski, 2012). To predict the behavior of others, perceivers regularly employ biased strategies to collect and interpret information that corresponds to their expectations (Lord et al , 1979; Johnston and Macrae, 1994; Frimer et al , 2017; Falben et al , 2019; Oyserman and Yan, 2019). Here we provide evidence to suggest that humans associate expectation-consistent information with intrinsic value, much like other forms of reward such as food or money.…”
Section: Discussionmentioning
confidence: 99%